Prostate Cancer Prevention, Diagnosis and Treatment - Brooks, James D. MD.; Stanford University. Medical Center (Stanford, CA : Stanford Video, 2005)
Prostate cancer is the most commonly diagnosed cancer in men in the United States. This program focuses on what is known about preventing cancer, current diagnostic techniques and the variety of treatment available.
DVD.
107996
Keywords: Prostate; Prostatic neoplasms; Prostatic diseases